1981
DOI: 10.1016/s0022-5347(17)55205-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Electrical Nerve Stimulator for Stress Incontinence

Abstract: It has been shown that some patients with stress incontinence after prostatectomy may have significant improvement with electrical anal stimulation. The use of a transcutaneous stimulator is the easiest and least invasive method to try initially. Results may be quite satisfying whether the mechanism is physiologic or placebo. This is the first report of the use of transcutaneous electrical nerve stimulation in patients with stress incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Whether the application of TENS to sacral dermatomes has a mode of action similar to direct sacral root stimulation is at present unknown. Perianal TENS has been used to good effect in the treatment of stress incontinence following prostatectomy, the authors reporting an increase in sphincter electrical activity in some patients, although it is of interest that there was no significant change in the urethral pressure profile measured during stimulation [20].…”
Section: Mode Of Action Of Tensmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether the application of TENS to sacral dermatomes has a mode of action similar to direct sacral root stimulation is at present unknown. Perianal TENS has been used to good effect in the treatment of stress incontinence following prostatectomy, the authors reporting an increase in sphincter electrical activity in some patients, although it is of interest that there was no significant change in the urethral pressure profile measured during stimulation [20].…”
Section: Mode Of Action Of Tensmentioning
confidence: 99%
“…The use of TENS in men with stress incontinence following simple or radical prostatectomy has been described with 75% having some improvement in continence [20]. The benefit persisted for 7 months after discontinuation of stimulation in 1 of the men.…”
Section: Stress Incontinencementioning
confidence: 99%
“…Recently, the Easy-K (Alphamedic Co., Ltd., Daegu, Korea) device was designed for contracting the PFM by electrical stimulation using cutaneous perivaginal electrodes in the sitting position. Previous studies suggest that TES is effective in treating urinary incontinence and can be performed using cutaneous electrodes in the perivaginal region [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported the effects of surface electrical stimulation in the supine or hook-lying position for treating urinary incontinence, which can be performed with placement of cutaneous electrodes in the perivaginal or sacral region [7,11,12]. Because PFM contraction in sitting or upright position was more di cult than hook-lying and supine position by vaginal squeeze pressure data [13], symptoms related to SUI could be occur mostly in sitting and standing.…”
Section: Introductionmentioning
confidence: 99%